APLIKASI DAN KARAKTERISASI EDIBLE FILM DARI KARAGINAN (Eucheuma cottonii) PADA BUAH - Nasution, Reni Silvia (AMINA, 2019)
Fruits are perisbable comestible that having short shelf life. The disadvantage of fruits since post harvest to received by consumers in quantity and quality is caused by microorganisms, insect, and the conditions of distribution and storage. Carrageenan edible film packaging is one of proper alternative to increase endurance and shelf life of fruits. It also becoe a solutio for undegradable plastic packaging that causing environmental pollution. Characterization which is common being conducted to edible film are mechanic properties (tensile strength and elongation break), thickness, solubility, water and vapor permeability rate. Several studies show that fruits with carragenan edible film and coating increase the perishable significanly comparing to uncoated fruits (control), so that it could lengthen the shelf life, reduce disappear of the odor,slow down colour change and gase transfer.